Mirror writing after perimesencephalic subarachnoid haemorrhage. (June 2019) - Fleming, Benjamin; Adamides, Alexios A.
Highlights: Caucasian right-handed woman exhibited transient mirror writing. Mirror writing occurred following a perimesencephalic haemorrhage. No lateralising lesion has been identified to explain this phenomenon. Radiological features and hyponatraemia suggested mirror writing could have been due to cerebral ischaemia. Hyponatraemia might have portended delayed ischaemic neurological deficit. Abstract: We report a case of a right-handed Caucasian woman who developed mirror writing following a non-aneurysmal, non-traumatic subarachnoid haemorrhage. The patient was unaware of having this phenomenon, and it was detected by clinical staff when the patient was writing a card to a family member. Serial imaging has ruled out a stroke as well as an underlying vascular abnormality. This phenomenon resolved after two months. Whilst there is a body of literature surrounding mirror writing, to our knowledge, this is the first description of mirror writing in the setting of a perimesencephalic subarachnoid haemorrhage.